Les représentations du changement dans la société qatarie, d’un émir à l’autre (1972–2013) - Anie Montigny (Arabian Humanities)
Since the independence of the country in 1971 and until June 2013, Qatar was ruled by two Emirs both of whom had undergo significant transformations. The aim of the paper is to understand how these transformations have been experienced, perceived and committed to memory by the Qataris. The representations born out of these were the subject of anthropological investigations that were followed-up, thereby granting the anthropologist the position of both actor and witness.Our working hypothesis is that the changes called for in the name of progress on the one hand, and the discourses on the need to uphold tradition — the tribes play their part in this — on the other hand, are constants from one emir to the other. Our paper highlights the fact that, between the two emirs (father and son), their people's assessment has a lot to do with the pace of reforms in various spheres.